It is not about the treasure, it is about the hunt -engaging students through gamification / Nurul Asyikin Md Zaki, Syafiza Abd Hashib and Ummi Kalthum Ibrahim - Md Zaki, Nurul Asyikin; Hashib, Syafiza Abd; Ibrahim, Ummi Kalthum (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Implementation of the engineering programme has been primarily based on traditional approach to teaching and learning for decades. Nonetheless, immersive classroom learning that actively and cooperatively includes students' participation has been reported to enable them to improve their creativity, problem solving and critical thinking skills, which are required in the top ten skills today. The introduction of gamification of learning is an innovative approach in improving students' opportunities to learn and develop skills through a positive, engaging learning environment. The gamification strategy further seeks to bring about changes in the involvement and success of students in the Food Preservation Technology course. Perceptions and feedback from the students were obtained through questionnaires and reflective assessment. Most students prefer classroom approach with a gamification environment. Gamification creates flexibility and makes the course more enjoyable for both students and instructors.